‘Het is een stadswerk, daar word niet nagesien’. Aspects of building policy and practice of towns in the province of Holland during the eighteenth century (Bulletin KNOB, 2005)
In general, the eighteenth century in Holland is regarded as a period of decline after the great prosperity and affluence of the preceding century. The number of public works in towns in Holland decreased and the urban building companies concentrated on maintenance of existing structures. In the course of this century many towns were faced with increasing financial deficits.The direct connection between public funds and public works, which made up twenty to thirty per cent of the total expenditure, made interventions in the building companies necessary. The high cost and often qualitatively poor execution of public works caused the town administrations to distrust the officials involved.Several towns carried out reorganisations, in which the urban building company was sometimes closed down completely. Besides, new procedures and bureaucratic measures were prescribed in order to get more grip on the building company, and thus on town expenses. Open tendering of maintenance work to private bosses was expected to be very advantageous.The reforms mentioned were not exclusively aimed at saving expenses, but also at improvements in the execution. However, in general the interventions had the opposite effect. This had to do with the lack of knowledge of the town administrations as regards the building trade in general and their own building company in particular. Public building proved to be very susceptible to fraud.Occasional successes depended more on the individual commitment of competent administrators or officials than on a newly conceived form of organisation. On the basis of some reorganisations of urban building companies and some building projects in Delft, Leiden, Haarlem and Schiedam this article gives a picture of the problems which town administrators were faced with in connection with public works.